2018
DOI: 10.1007/s00259-018-4119-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying SV2A density and drug occupancy in the human brain using [11C]UCB-J PET imaging and subcortical white matter as reference tissue

Abstract: This [C]UCB-J blocking study validated SO as a suitable reference region for non-invasive quantification of SV2A availability and drug occupancy in the human brain. Accurate quantification can be achieved by using either SUVR with a 60-90 min PET acquisition or SRTM BPwith at least 70 min dynamic PET acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 23 publications
3
83
1
Order By: Relevance
“…Although no known reference region exists for 18 F-BCPP-EF, we found that V T estimates were about 50% lower in the centrum semiovale than in gray matter regions. 11 C-UCB-J V T estimates were about 60% lower in the centrum semiovale than in gray matter regions, supporting previous suggestions of its potential use as a reference region for 11 C-UCB-J (33). Blocking studies with specific MC1 and SV2A compounds should be conducted in both healthy and disease cohorts to confirm the viability of the centrum semiovale as a reference region.…”
Section: Discussionsupporting
confidence: 77%
“…Although no known reference region exists for 18 F-BCPP-EF, we found that V T estimates were about 50% lower in the centrum semiovale than in gray matter regions. 11 C-UCB-J V T estimates were about 60% lower in the centrum semiovale than in gray matter regions, supporting previous suggestions of its potential use as a reference region for 11 C-UCB-J (33). Blocking studies with specific MC1 and SV2A compounds should be conducted in both healthy and disease cohorts to confirm the viability of the centrum semiovale as a reference region.…”
Section: Discussionsupporting
confidence: 77%
“…In Cohorts 2 and 3, V T values were computed using the 1TC model to fit regional time‐activity curves . The V T estimate was derived from the model fit parameters, K 1 and k 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In Cohorts 2 and 3, V T values were computed using the 1TC model to fit regional time-activity curves. 21,22 The V T estimate was derived from the model fit parameters, K 1 and k 2 . Regional V T values were computed for 23 regions, including amygdala, anterior cingulum, anterior insula, caudate nucleus, cerebellum, dorsolateral prefrontal cortex, frontal cortex, fusiform, globus pallidus, hippocampus, insula, occipital cortex, orbitofrontal cortex, parahippocampal gyrus, parietal cortex, posterior cingulum, posterior insula, putamen, substantia nigra, temporal cortex, thalamus, ventromedial prefrontal cortex, and ventral striatum.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Regional time-activity curves were extracted with and without correction for cerebrospinal fluid (CSF) partial volume using the SPM12 CSF probability map, again smoothed to PET resolution. To quantify SV2A density, [ 11 C]UCB-J non-displaceable binding potential (BP ND ) was determined using a basis function implementation of the simplified reference tissue model (Wu and Carson, 2002), with the reference tissue defined in the centrum semiovale (Koole et al, 2019;Rossano et al, 2019). Group average BP ND images (illustrated in Fig1 A-C) were obtained by spatially normalizing individual T1weighted MRI (and thereby co-registered BP ND map) to MNI space, and then to the group template using ANTS.…”
Section: Neuroimagingmentioning
confidence: 99%